URBAN GEOLOGY 5. Edmonton Landfill Site Investigation: A Case Study Applying Hydraulic Information to Interpret a Glacially Disturbed Site - Andriashek, Laurence; Thomson, David; Jackson, Reed (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1993)
Summary Detailed characterization of the hydro-geologic setting was essential to model the potential for leachate migration from the proposed City of Edmonton Waste Management Centre at the Aurum site. Conventional geologic information from bore holes limited the ability to provide a detailed interpretation of stratigraphie units made geologically complex by glacial over-riding and thrusting. Supplementary information from hydraulic tests proved to be crucialin resolving difficulties in correlation of hydrostratigraphic units as additional geologic data became available. Piezo-meter readings and pumping tests established that two discrete aquifers a represent within an apparently single hydrostratigraphic unit. Glacialice thrusting and injection of a slab of displaced bedrock effectively severed the unit into two aquifers with dissimilar hydraulicproperties.